2005
DOI: 10.1063/1.2012512
|View full text |Cite
|
Sign up to set email alerts
|

Temperature study of the spin-transfer switching speed from dc to 100ps

Abstract: We study the speed of the magnetization switching resulting from spin transfer in pillar-shaped CoFe∕Cu∕CoFe spin valves and the temperature dependence thereof. The switching speed was investigated with current pulses of durations from 100ps to dc while the temperature was varied from 50to300K. Quasistatic loops indicate that the reversal events imply transition states with reduced remanences. Their interval of occurrence shrinks gradually to almost null when the temperature is raised to 300K. The curvature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
40
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 17 publications
7
40
1
Order By: Relevance
“…However, previous investigations have concluded that the reversal speed in the sub-ns regime has insufficient reproducibility. This has first been interpreted qualitatively as resulting from classical thermal fluctuations [11], but reliable predictions are not yet available .…”
Section: /13mentioning
confidence: 99%
“…However, previous investigations have concluded that the reversal speed in the sub-ns regime has insufficient reproducibility. This has first been interpreted qualitatively as resulting from classical thermal fluctuations [11], but reliable predictions are not yet available .…”
Section: /13mentioning
confidence: 99%
“…The fastest precessional reversal demonstrated experimentally using an external magnetic field 2,3 is ∼100 ps, with similar reversal times achieved using a spin-polarized current. [4][5][6] Recent experimental work in the field of magneto-optics has demonstrated that carefully shaped laser pulses can be used to manipulate the magnetization dynamics on the subpicosecond time scale [7][8][9][10][11][12] in many materials, including cobalt, iron, nickel, and GdFeCo. However, controllable magnetization switching has only been observed in GdFeCo, and this has stimulated a great deal of effort to attempt on many levels to explain the process.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, STT requires huge current densities, which can lead to substantial heating and early material fatigue. STT may also assist the magnetization switching in nanopillar geometries [4,5], and it can increase the magnetization thermal noise [6], degrading the device performances. In nanopillar geometries, the magnetization dynamics takes place in a very confined region where the temperature is almost uniform [7], such that the temperature dynamics could be understood from simple experiments [5].…”
mentioning
confidence: 99%